Hubungan Pengetahuan tentang Bahaya Alkohol dengan Sikap Remaja Laki-laki dalam Mengonsumsi Alkohol - Uswatun Hasanah; Sebastinus Kurniadi Tahu; Sakti Oktaria Batubara; Yohanes Dion (Universitas Insan Budi Utomo, 2026)
A preliminary study conducted on seven students at SMKN 2 Kupang, found variations in the level of knowledge and attitudes of adolescents towards alcohol consumption. This study aims to determine the relationship of knowledge about the dangers of alcohol with adolescent attitudes in consuming alcohol in adolescent boys in SMKN 2 Kupang. This study is a quantitative study with correlational design and cross-sectional approach that aims to determine the relationship between knowledge about the dangers of alcohol with adolescent attitudes in consuming alcohol. The study was carried out at SMKN 2 Kupang in December 2025 with a sample of 244 respondents taken using proportional random sampling and simple random sampling techniques. Data collection was carried out using questionnaires, namely knowledge questionnaires and attitude questionnaires. Data analysis was conducted univariate and bivariate using Spearman Rank test (Spearman's rho) with significance level of 0.05. The results showed the level of knowledge about the dangers of alcohol adolescent boys in SMK Negeri 2 Kupang classified in the good category. 47.5% of respondents strongly agree that consuming alcohol can damage organs such as the liver and brain. In addition, as many as 42.2% of respondents responded that they prefer to avoid friends who like to consume alcohol. There is a significant relationship between knowledge about the dangers of alcohol with adolescent attitudes in consuming alcohol in adolescent boys in SMKN 2 Kupang.